The atomistic level structure for the activated human κ-opioid receptor bound to the full Gi protein and the MP1104 agonist - Mafi, Amirhossein (Proc Natl Acad Sci U S A, 2020)
The kappa opioid receptor (κOR) is an important target for pain therapeutics to reduce depression and other harmful side effects of existing medications. The analgesic activity is mediated by κOR signaling through the adenylyl cyclase-inhibitory family of Gi protein. Here, we report the three-dimensional (3D) structure for the active state of human κOR complexed with both heterotrimeric Gi protein and MP1104 agonist. This structure resulted from long molecular dynamics (MD) and metadynamics (metaMD) simulations starting from the 3.1-Å X-ray structure of κOR–MP1104 after replacing the nanobody with the activated Gi protein and from the 3.5-Å cryo-EM structure of μOR–Gi complex after replacing the 168 missing residues. Using MD and metaMD we discovered interactions to the Gi protein with strong anchors to two intracellular loops and transmembrane helix 6 of the κOR. These anchors strengthen the binding, contributing to a contraction in the binding pocket but an expansion in the cytoplasmic region of κOR to accommodate G protein. These remarkable changes in κOR structure reveal that the anchors are essential for activation.